(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Increasing prevalence of carbapenem-resistant Pseudomonas species and Acinetobacter species in the nosocomial setting represents as emerging challenge to public health. The frequency of carbapenemase producing strains among clinical isolates has been steadily increasing over the past few years resulting in limitation of the therapeutic options. Objective: This study was conducted to determine the prevalence of carbapenemase producers in urine and wound-swab along with antimicrobial resistance patterns of these organism. Methodology: This was a cross sectional study which was done in the department of Microbiology of Chittagong Medical College with 300 patients from February 2021 to June 2022. Nonduplicate Pseudomonas species and Acinetobacter species. were included in this study from inpatients of Chittagong Medical College Hospital. Antimicrobial susceptibility test was performed by Kirby Bauer disc diffusion method as per Clinical Laboratory Standard Institute-2021 The modified carbapenem inactivation method was done to see carbapenemase producers among meropenem resistant isolates. Finally carbapenemase genes were detected by multiplex PCR. Results: Out of 300 samples, 171 culture positive isolates showed 38.01% Pseudomonas species11.11% Acinetobacter species and along with 51.39% other species. Following CLSI guideline 2021 antimicrobial susceptibility tests revealed that highest resistance against ampicillin,cefuroxime, ciprofloxacin, astreonam, ceftriaxone and ceftazidime were 98.80%, 77.38%,73.80%, 70.23%, 69.04% and 67.85% respectively. The lowest resistance was observed against nitrofurantoin, amikacin, pipercillin-tazobactum, meropenem and cefipime11.90%, 16.66%, 22.61%, 27.38% and 39.24% respectively.Also,21.17% were found to be carbapenemase producers by mCIM and 24.70% carbapenemase genes were detected by multiplex PCR among meropenem resistance isolates. Multiplex PCR showed blaNDM gene in 95.23% isolates, bla-VIM in 4.77% among meropenem resistance isolates. Conclusion: In conclusion the frequency of carbapenemase producing Pseudomonas species and Acinetobacter species is increasing which causes a significant impact on patient′s management. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):18-25